On To Mars! Chronicles of Martian Simulations - PLETSER, Vladimir (Springer Singapore, 2018)
This book introduces the Martian simulations, one installed on Devon Island, an uninhabited island in the Canadian Arctic, well within the polar circle, and two in the desert of Utah, several hundreds of kilometers South of Salt Lake City. The book is based on the diaries during the simulations, held by Vladimir Pletser, a physicist-engineer, who was selected to attend these simulations. It relates the details of everyday life in these Martian habitats and of the scientific and exploratory work conducted in these extreme environments in preparation for future manned missions to Mars. Through the real experiences described in the book, readers will find space explorations and living on Mars more tangible. .